DEFINITION OF THE STATUS OF “I” AND “THE OTHER”: FIRST TRIES OF GERMAN DIALOGISM OF THE BEGINNING OF XX CENTURY AND M. BACHTIN’S DIALOGISM - Бобровський, О. Є. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Author of the article puts the light on two lingual – dialogical approaches to define “I” of Human Being and “the Other”. In spite of the fact that F. Ebner’s harmonic – tragic “I” is defined only through “Thou” but for the M. Bachtin individualistic personification “I-for-myself” is the outcome of being aware of the others that are different from me as “active spots I”” two philosophers use the language as tool for action and interrelationships as with surrounding so with the “Other”.